The benefits of hypothermic machine preservation and short cold ischemia times in deceased donor kidneys - Kox, J; Moers, C; Monbaliu, D; Strelniece, A; Treckmann, J; Jochmans, I; Leuvenink, H; Van Heurn, E; Pirenne, J; Paul, A; Ploeg, R (Wolters Kluwer, 2018)
Background Hypothermic machine perfusion (HMP) of deceased donor kidneys is associated with better outcome when compared to static cold storage (CS). Nevertheless, there is little evidence whether kidneys with short cold ischemia time (CIT) also benefit from HMP and whether HMP can safely extend CIT. Methods We analyzed prospectively collected data from the Machine Preservation Trial, an international randomized controlled trial. Seven hundred fifty-two consecutive renal transplants were included: 1 kidney of each of the 376 donors was preserved by HMP, the contralateral organ was preserved by CS. Results The mean CIT was 3:05 PM (SD, 4:58 AM). A subgroup analysis was performed, groups were based on CIT duration: 0 to 10 hours, 10 to 15 hours, 15 to 20 hours, or 20 hours or longer. Delayed graft function (DGF) incidence in the subgroup with up to 10 hours CIT was 6.0% (N = 3/50) in the HMP arm and 28.1% (N = 18/64) in the CS arm (univariable P = 0.002; multivariable odds ratio [OR], 0.02; P = 0.007). Cold ischemia time remained an independent risk factor for DGF for machine perfused kidneys recovered from donation after brain death donors (OR, 1.06; 95% confidence interval [CI], 1.017-1.117; P = 0.008), donation after circulatory death donors (OR, 1.13; 95% CI, 1.035-1.233; P = 0.006) and expanded criteria donors (OR, 1.14; 95% CI, 1.057-1.236; P = 0.001). Conclusions In conclusion, HMP resulted in remarkably lower rates of DGF in renal grafts that were transplanted after a short CIT. Also, CIT remained an independent risk factor for DGF in HMP-preserved kidneys.